2022
DOI: 10.1136/bmjopen-2022-065605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stroke and associated risk factors: a population-based cross-sectional study from the Qinghai-Tibet Plateau of China

Abstract: Background and objectivesThe epidemiology of stroke at high altitudes has not been extensively studied, especially at heights of 4000 m and above. Thus, stroke prevention and treatment at high altitudes are challenging. We conducted a cross-sectional study to estimate the prevalence of stroke, the detection rate of individuals at high risk of stroke and the risk factors for stroke in the Qinghai-Tibet Plateau in China, a high altitude plateau that inhabits approximately 15 million people.DesignA population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Based on the subgroup analysis, we discovered that Hans individuals were more likely to have hypertension. ZhenHua Li et al reported the same result [16]; however, they did not explain their findings. To further understand the difference between the Tibetan and Hans populations, we compared their characteristics (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 85%
“…Based on the subgroup analysis, we discovered that Hans individuals were more likely to have hypertension. ZhenHua Li et al reported the same result [16]; however, they did not explain their findings. To further understand the difference between the Tibetan and Hans populations, we compared their characteristics (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 85%
“…After screening the titles and abstracts, 692 papers were deemed ineligible. Following further evaluation and selection, a total of 17 papers4 10–25 that met the inclusion criteria were included in our quantitative synthesis (figure 1). The characteristics of the included studies can be seen in online supplemental table S2.…”
Section: Resultsmentioning
confidence: 99%
“…In Jiangsu Province, China, a populationbased study reported 740 (1.9%) stroke events, 13.2% of which were reported to be hemorrhagic stroke, while 86.8% of a total population of 39887 adult individuals had ischemic stroke [25]. Another crosssectional study conducted in Qinghai, China, reported that the prevalence of stroke was 2.3% in a population of 10,700 adults, where dynamism also increased from low-altitude regions to high-altitude regions [26].…”
Section: Association Of Lipid Profile Abnormalities and Cvdsmentioning
confidence: 99%